2022
DOI: 10.1021/acs.inorgchem.1c03167
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Color Emission of Mechanoluminescence and Photoluminescence from SrZnSO: Bi3+ for Multimode Anticounterfeiting

Abstract: Mechanoluminescence materials that emit light under mechanical stimulation have attracted widespread attention in sensing, anti-counterfeiting and imaging applications. In this study, a series of novel Sr1-xBixZnSO (0.001≤x≤0.1) samples were synthesized by the method of high temperature solid-state reaction. It is worth noting that the distortion degree of SrO3S3 octahedron was increased with increasing Bi 3+ concentration, and the color manipulated Sr1-xBixZnSO which can emit different photoluminescence (blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Furthermore, Er 3+ also regulates the trap density, which determines the intensity of ML. [ 39 ] Concentration quenching is a competitive process between the rate of depopulation of the active energy level, and the rate of carrier injection. The amount of injected carriers can be changed through changing the energy migration path.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Er 3+ also regulates the trap density, which determines the intensity of ML. [ 39 ] Concentration quenching is a competitive process between the rate of depopulation of the active energy level, and the rate of carrier injection. The amount of injected carriers can be changed through changing the energy migration path.…”
Section: Resultsmentioning
confidence: 99%
“…The photoluminescence properties of Bi 3+ -substituted phosphors are also influenced by mechanical stress such as compression, distortion, stretching, and bending. Indeed, several previous reports confirmed that the photoluminescence emission color of a Bi 3+ -substituted phosphor was drastically changed when the material was ground in a mortar or scratched with a pencil. Although those MCL materials have great potential for application not only as a simple pressure sensors but also as detectors of internal stress or cracks in transparent materials in non-destructive inspection, manipulation of MCL materials is still challenging due to their low reversibility and the difficulty of correlating the MCL intensity with stress intensity. Moreover, the fragile nature of ceramics has greatly hampered developments in the MCL field using inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The energy transfer gives rise to a concentration quenching effect, leading to a decrease in the PL intensity. Using the Blasse formula, the critical distance R c for energy transfer between Bi 3+ ions can be calculated and the mechanism of the concentration quenching can be described as: 33,34 where x c = 0.06 is the critical concentration, V = 682.375 Å 3 is the cell volume and N = 4 is the number of cations per unit cell of SLSO:Bi 3+ . The calculated R c is approximately 17.58 Å, much larger than the critical concentration of 5 Å for exchange interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The energy transfer gives rise to a concentration quenching effect, leading to a decrease in the PL intensity. Using the Blasse formula, the critical distance R c for energy transfer between Bi 3+ ions can be calculated and the mechanism of the concentration quenching can be described as: 33,34…”
Section: Dalton Transactions Papermentioning
confidence: 99%